ANALISIS PENGOLAHAN IKAN BANDENG OLEH MASYARAKAT DI DESA DUKUNANYAR (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Dukunanyar is a village which is located in the capital of Dukun Region. It consists 1,574 citizens. In this village, there are several organizations such as residence organization, family empowerment and prosperity, and religious groups. Prior to the program, the headman of Dukunanyar Village asked if the students could maximize the local potential and empower the women there. Milkfish is one of the local potentials in Dukunanyar Village. A milkfish contains 14,2% of omega-3 and 20% of protein. Unfortunately the percentage of childrenâ€™s milkfish consumption in Dukunanyar Village is low due to its spine. Therefore we trained the women (mother) to cook new varieties of milkfish namely Abon and Sempol of Milkfish. Abon are usually made of beef, while Sempol are made of chicken. The result of our program is the women in Desa Dukunanyar were enthusiast and are driven to cook milkfish for their family. Furthermore they are going to build their own business. It is proved by â€œAbon Bandengâ€ product which made by the women of family empowerment and prosperity in the second neighborhood in Dukunanyar Village